Manajemen Pelayanan Rumah Sakit Umum Daerah (RSUD) Kota Dumai - Khairatun Nisa; Harapan Tua RFS (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The hospital is one of the organizations in the service sector that is engaged in efforts to improve public health. In addition, the hospital as oe of the subsystems of health services provides two types of services for the community, namely health services and administrative services. Therefore, as a hospital service institution, it is required to improve its service quality management continuously and continuously in various fields of service provided. So the Dumai City Hospital should be able to provide good service to pattiens with planned management for class B classified hospitals. The purpose of this study was to find out how the management of outpatient services in the field of pregnancy at the Regional General Hospital in Dumai City. This research method uses qualitative research methods with data collection thechniques using primary data and secondary data obtained from the results of observations, interviews, and documentation that the researcher analyzed in obtaining the data. This study uses the theory of Ratminto about service management, namely planning, implementation, and coordination. The results of the study indicate that the service management of the Dumai City Regional Public Hospital still has obstacles in its services such as training of workers who have not all received training, budget, facilities and infrastructure.